Pengenalan Komponen Elektronika Raspberry Pi Untuk Kalangan Siswa dan Siswi di Kembangan Utara - Lukman Medriavin Silalahi; Imelda Uli Vistalina Simanjuntak; Freddy Artadima Silaban; Setiyo Budiyanto; Dimas Jatikusumo; Muhammad Ikhsan; Agus Dendi Rochendi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
Industry demand for skilled human resources presents a challenge for every school graduate to conduct various competency and skills training. So, the solution to meet industry challenges is a training on the application of science and technology for the community entitled